AN EVALUATION OF INNOVATE TEACHING TECHNIQUES AMONG EDUCATIONLIST IN ARTS AND SCIENCE COLLEGE OF KANYAKUMARI DISTRICT (International Journal of Food and Nutritional Sciences, 2022)
Education is the process of facilitating the development of one's knowledge, abilities, convictions, and routines. It's essential that the two fundamental components of education—transmitting and absorbing information—be equal in importance. A good teacher tries his or her utmost to convey material in the same way in which the instructor has learned it. The purpose of school is not only to teach pupils to read and write, but also to develop in them the skills they'll need to succeed in the real world. The effectiveness of a teacher and the cutting-edge techniques they use in the classroom determine a student's success. In addition to improving education, the adoption of innovative techniques in educational institutions has the potential to enhance governance, empower individuals, and energise efforts to meet the nation's human development objective. This study examined teachers’ views on the innovative techniques, for that 90 Assistant Professors opinion has been collected and analyzed by researcher. For that Percentages and t-test were applied.